CORRELATION BETWEEN THE PRESENCE OF ANDROGENIC RECEPTORS AND MOLECULAR AND HISTOPATHOLOGICAL VARIABLES IN BREAST CANCER - Geronymo, Beatriz Baaklini; Carvalho, Filomena Marino; Yoshimura, Adriana Akemi; Andrade, Juliana Zabukas de; Andrade, Danúbia Ariana de; Barros, Alfredo Carlos Simões Dornellas de (Mastology, 2021)
Introduction: The expression of androgenic receptors (AR) is a new predictive marker of response and prognosis in invasive breast carcinoma (BC). It emerges as a potential therapeutic target. Objectives: To evaluate the frequency of AR positivity and its correlation with molecular and histopathological parameters in infiltrative BC. Methods: Retrospective cohort study, analyzing 119 cases of non-metastatic invasive BC, seen at a private clinic. Hormonal receptors were screened by immunohistochemical reaction, and AR were considered positive when present in at least 10% of cells, ER and PR from 1%. This finding was correlated with pathological staging, histological grade (HG), vascular-lymphatic invasion (VLI), estrogen receptors (ER), progesterone receptors (PR), HER2 and Ki 67. Results: AR were positive in 96 cases (80.6%). The correlation with the surveyed parameters can be seen in the table. Conclusions : AR positivity is associated with more differentiated hormone-dependent tumors and with a lower proliferation rate.